"Relief-Retaining" Control Technology of Floor Heave in Mining Roadway with Soft Rock: A Case Study. (23rd November 2021) - Chen, Ai; Li, Xuebin; Liu, Xuesheng; Tan, Yunliang; Xu, Ke; Wang, Honglei
Abstract : The floor heave problem is one of the important factors affecting the stability and safety of surrounding rocks of roadways, especially in deep high-stress mining roadway with soft rock. The return airway of no. 130203 working face in Zaoquan Coal Mine of Ningdong Mining Area in Northwest China is the research object in this study. Firstly, an innovative "relief-retaining" control scheme of floor heave is proposed, which is the comprehensive measure of "cutting groove in floor + drilling for pressure relief at roadway side + setting retaining piles at the junction of roadway side and floor." Then, the specific parameters suitable for floor heave control of no. 130203 return airway are determined using numerical simulation method. Finally, the yield monitoring results show that both the deformation of surrounding rocks and the cable force are significantly reduced. The roof falling capacity, floor heave displacement, and thickness increasing value of 0–2 m floor strata are 596 mm, 410 mm, and 82 mm, respectively, which are 43.67%, 67.49%, and 75.38% less than those of the control section. The maximum force of cables at roadway sides is 140.13 kN, about 32.54% less than that of the control section. The results verify the reliability of the proposed "relief-retaining" control scheme and can provide some reference for the floor heave control of similar roadways.